Analisis Inovasi Pendidikan IPA Berdasarkan Pendekatan STEAM: Kajian Literatur Sistematis - Shofia Maghfiroh; Insih Wilujeng; Suyanta; Sabar Nurohman; Sri Rejeki Dwi Astuti (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to find out various kinds of science learning innovations and educational developments using the STEAM approach. The method used in this research is a systematic literature review by analyzing 23 Scopus-indexed articles and 7 Sinta-indexed articles. The results of the study show that science learning is developed on the STEAM approach implementing learning applications that are integrated with traditional musical instruments, integration strategies, SSIT-based, traditional sciences, professional development pathways, implementation PjBL Learning model, and Next Generation Science Standards (NGSS). The development of education in the STEAM approach is very rapid, it is evident that the level of success of teachers in STEAM-based learning increases the ability of students both in terms of cognitive, psychomotor, and affective. It can be interpreted that the application of the STEAM approach is very important to improve the success of the quality of education on a small or large scale.